Beginning Windows 8 application development : XAML edition - Burns, Kyle (Expert's voice in .NET., 2012)
Beginning Windows 8 Application Development - XAML Edition introduces you to the Windows 8 modern app design paradigm and the new Windows 8 programming model developed around this paradigm. You'll learn to build rich, immersive applications designed to run on the many devices that will be powered by Windows 8. With the introduction of Windows 8, once again Microsoft has re-envisioned the way that PCs and devices will be used and applications will be built in a world that has become far more connected. The Windows 8 modern UI style is far more than a programming model and Beginning Windows 8.